The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1002/anie.201510354
|View full text |Cite
|
Sign up to set email alerts
|

Copper‐Catalyzed Borylcupration of Allenylsilanes

Abstract: A highly regio- and stereoselective copper-catalyzed borylcupration of 1,2-allenylsilanes affords an unexpected regioreversed allylic boronate bearing an extra C-Si bond at the 3-position, with a thermodynamically disfavored Z geometry. Such stereodefined allylic boronates containing an extra alkenyl silane moiety are very useful organodimetallic reagents for organic synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 56 publications
1
18
0
Order By: Relevance
“…Our initial attempts began with the coupling reaction of allenyl-vinylsilane 1a [22] with phenylboronic acid 2a and Pd(OAc) 2 (5 mol %) as the catalyst( Scheme3). [20e] To our delight, the reaction in THF with BQ (BQ = p-benzoquinone, 1.1 equiv) as the oxidanta fforded tetrasubstituted olefin 3aa in 26 %y ield.…”
Section: Resultsmentioning
confidence: 99%
“…Our initial attempts began with the coupling reaction of allenyl-vinylsilane 1a [22] with phenylboronic acid 2a and Pd(OAc) 2 (5 mol %) as the catalyst( Scheme3). [20e] To our delight, the reaction in THF with BQ (BQ = p-benzoquinone, 1.1 equiv) as the oxidanta fforded tetrasubstituted olefin 3aa in 26 %y ield.…”
Section: Resultsmentioning
confidence: 99%
“…Ma and co-workers found that a silyl-substituted allene as the starting reagent afforded a hydroborated product containing an allylborane moiety [Scheme 9 (a)]. 20 In the reaction, borylcupration took place, affording a vinylcopper intermediate that was confirmed by a deuterium-labelling experiment. In contrast, they also reported the borylation of allenylsilanes to afford vinylboronates with an allylsilane moiety [Scheme 9 (b)].…”
Section: Syn Thesismentioning
confidence: 99%
“…Yoshida and co-workers reported the carboboration of allenes, by applying their knowledge of carboboration with alkenes to allenes. 29 As shown in Scheme 18, the reaction of allene 3d with an unsymmetrical diboron reagent, (pin)B-B(dan), in the presence of benzyl chloride (20) as an electrophile afforded the desired product 21 when employing dppf as the ligand.…”
Section: Review Syn Thesismentioning
confidence: 99%
“…In addition to the aforementioned enantioselective processes, there have been reports of the non-enantioselective copper-catalysed functionalisation of allenes that enables access to diversely functionalised molecules that are ripe for the development of enantioselective variants. As well as the silylative variants of the aforementioned borylative couplings of aldehydes, 26 ketones 27 and imines, 21 described above, such copper catalysed functionalisations of allenes include protoboration that selectively delivers alkenyl or allylic boronic esters, 28 borostannylation that yields β-boryl allyl stannanes, 29 hydrocupration followed by branch selective imine allylation, 22 carboboration that produces alkenyl boronic esters, 30 intramolecular hydroamination for the formation of 3-pyrrolines or 2-alkenylpyrrolidines, 31 and conjugate addition type processes of allenoates and their derivatives. 32 …”
Section: Future Prospects In Copper Catalysed Allene Functionalisatiomentioning
confidence: 99%